Teacher's efforts in improving the social-emotional development of elementary school-aged children - Sadiah, Tia Latifatu; Dewi, Sinta Maria; Nur DS, Yulistina (Universitas Wiralodra, 2023)
This research aims to discover how the teacher's efforts improve the social-emotional development of elementary school children in grade II at Sdn Karawang Kulon 1 during learning. This research uses descriptive qualitative research. The ability of children's social-emotional relations develops because of their curiosity about everything in the world around them. Social-emotional development involves relationships and interactions with other people through the feelings expressed by someone towards other people, be they happy or sad feelings. This research uses descriptive qualitative research. The ability of children's social-emotional relations develops because of their curiosity about everything in the world around them. Social-emotional development involves relationships and interactions with other people through the feelings expressed by someone towards other people, be they happy or sad feelings. This research uses descriptive qualitative research. The ability of children's social-emotional relations develops because of their curiosity about everything in the world around them. Social-emotional development involves relationships and interactions with other people through the feelings expressed by someone towards other people, be they happy or sad feelings